2020
DOI: 10.5334/cie.20
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Reported Behavioural Changes in Children With Autism Spectrum Disorder During the COVID-19 Lockdown in Italy

Abstract: Autism Spectrum Disorders (ASD) are characterized by impairments in social interaction and reciprocal communication. During a pandemic, when social distancing becomes mandatory for all, both parents and children are not supported in-person by their therapists and cannot participate in usual therapies. This study reports the main clinical changes experienced by parents of children with during the first month of lockdown during the COVID-19 pandemic in Italy. Using standardized questionnaires, the families of 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 12 publications
6
62
1
5
Order By: Relevance
“…There have been studies conducted to examine the impact of the COVID-19 pandemic on autistic symptomology outcomes and some studies have reported mixed results. For example, Di Renzo et al [11] measured outcomes such as inflexible, repetitive behaviours, self-care skills, hyperactivity and sleep, and children's sensory profile using the parentreport Adaptive Behaviour Assessment System-II (ABAS-II) [12], the ASD Behaviour Inventory (ASDBI) [13], and the short sensory profile [14]. Results from the ASDBI [13] showed increased scores of hyperactivity, fear in new situations, sleep regulation problems, moodiness and irritability.…”
Section: Behavioural Outcomesmentioning
confidence: 99%
“…There have been studies conducted to examine the impact of the COVID-19 pandemic on autistic symptomology outcomes and some studies have reported mixed results. For example, Di Renzo et al [11] measured outcomes such as inflexible, repetitive behaviours, self-care skills, hyperactivity and sleep, and children's sensory profile using the parentreport Adaptive Behaviour Assessment System-II (ABAS-II) [12], the ASD Behaviour Inventory (ASDBI) [13], and the short sensory profile [14]. Results from the ASDBI [13] showed increased scores of hyperactivity, fear in new situations, sleep regulation problems, moodiness and irritability.…”
Section: Behavioural Outcomesmentioning
confidence: 99%
“…Therefore, the disruption to schools, minimised contact with peers, and reduced faceto-face support may have worsened the social communication challenges already experienced by a larger number of children living with ASD. In contrast, a recent study by Renzo et al (2020) indicated that despite behavioural problems worsening and symptomology intensifying in autistic children during the pandemic, parents reported improvements in their communicative relationships with their children. As a result, it is unclear what the actual impact of COVID-19 and the lockdowns may have been, and continue to be, for children diagnosed with ASD.…”
Section: Introduction Coronavirusmentioning
confidence: 72%
“…This may seem somewhat counterintuitive due to not being at school and socially isolating during the lockdown. However, Renzo et al (2020) reported that several parents, who completed their survey, noted an improvement in their child's verbal and non-verbal communication skills during the first month of lockdown in Italy. Our results indicated that over 90% of autistic children were not in school during the UK's first lockdown and many parents were often required to work from home or were furloughed during this lockdown period (Barker and Russell 2020, Burchell et al 2020, ONS 2020, Reuschke and Felstead 2020.…”
Section: Implications For Practice and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are also currently facing previously unknown situations like mass temporary unemployment, working from home, online homeschooling, rise in domestic violence, absolute lack of physical contact with friends/family, and restrictions within home space for prolonged periods (Colizzi et al, 2020;Di Renzo et al, 2020;Frankova, 2020;Kawabe et al, 2020;Parenteau et al, 2020). In parallel, fear of contracting the virus is still widely prevalent (Rajkumar, 2020;Roy et al, 2020;Singh et al, 2020).…”
Section: Slightly More Than Usualmentioning
confidence: 99%